Celebrating the Enigma: The Continuing Puzzle of the Toyota Production System - New, S (2007)
This introduction to the special issue celebrates the 30th anniversary of the publication of Sugimori et al. (Sugimori, Y., Kusunoki, K., Cho, F. and Uchikawa, S., Toyota production system and Kanban system: materialisation of just-in-time and respect-for-human system. Int. J. Prod. Res., 1977, 15(6), 553-564), the first extensive description of the Toyota Production System (TPS) to be published in English. After some initial discussion of the TPS, this article reviews three important issues regarding the context of the original paper: the West's growing interest in Japanese manufacturing; the preoccupation with information technology as the future of production; and, concerns with job design and motivation. The Sugimori paper is then analysed in these terms, focusing on the technical and human elements of the TPS. The article closes with an introduction to the other papers in the special issue. [ABSTRACT FROM AUTHOR]